In vitro Study of the Effects of Acetylcysteine on the International Normalized Ratio Over Time - Nazar, Messia; Kootstra-Ros, Jenny E; Touw, Daniel J; Sturkenboom, Marieke G G (Therapeutic drug monitoring, 2025)
Patients with paracetamol poisoning are treated with acetylcysteine. In paracetamol-poisoned patients without hepatocellular injury, an increased international normalized ratio (INR) was observed after acetylcysteine administration. Because INR is a marker of liver injury in paracetamol poisoning, assessing the magnitude of the effect of acetylcysteine treatment on INR is crucial. This in vitro study aimed to quantify the effects of clinically relevant concentrations of acetylcysteine on INR over time. Acetylcysteine (0-500 mg/L) in Omniplasma (pooled plasma) or citrate plasma from 6 healthy subjects was incubated at 37°C for up to 24 or 6 hours, respectively. Combined with acetylcysteine, the effects of paracetamol (0-200 mg/L), incubation temperature (37, 20, and 4°C), and tube size (15 and 2.5 mL) were investigated. Samples were drawn frequently and analyzed for INR. Citrate plasma from healthy subjects was used to assess interindividual variability. Data were analyzed using a generalized linear mixed model. At 37°C, every mmol/L (equals 163 mg/L) of acetylcysteine increased the INR with 0.039 (99% confidence interval [CI] 0.032-0.046, P < 0.0001), whereas every mmol/L (equals 151 mg/L) of paracetamol increased the INR with 0.028 (99% CI 0.013-0.044, P < 0.001). Independent of acetylcysteine and paracetamol, every hour of incubation at 37°C increased the INR by 0.012 (99% CI 0.011-0.014, P < 0.0001). Incubating 100, 200, and 500 mg/L acetylcysteine in plasma from healthy subjects at 37°C showed large interindividual variability in INR from 0.058 (99% CI 0.029-0.086, P < 0.001) to 0.173 (99% CI 0.131-0.216, P < 0.0001). This in vitro study showed a clinically significant effect of increasing acetylcysteine concentrations on INR over time at 37°C in pooled plasma. Additionally, a large interindividual variability was observed.